2017
DOI: 10.1002/dmrr.2874
|View full text |Cite
|
Sign up to set email alerts
|

Comparing glucose and hemoglobin A1c diagnostic tests among a high metabolic risk Hispanic population

Abstract: AIMS Compare HbA1c diagnostic tests for pre-diabetes and diabetes with plasma glucose criteria (PGC), and compare the metabolic profiles of people classified by HbA1c versus by glucose levels. METHODS Participants were recruited for the San Juan Overweight Adults Longitudinal Study (SOALS). Were primarily Hispanic (98%), without previously diagnosed diabetes, and aged 40–65 years. Participants classified as normal glycemic, pre-diabetes or diabetes based on baseline HbA1c and PGC, were compared with respect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 28 publications
1
6
1
Order By: Relevance
“…21 The high rates seen in the current study and in the AASK study (which was restricted to patients with both CKD and hypertension) are not surprising, as hypertension, CKD, and diabetes share common risk factors. The relatively low level of concordance among the measures of baseline glycemic control, consistent with other studies in high-risk 22 and patient (post-MI) 23 populations, raises questions about the best measure to use to characterize glycemic control status in persons with CKD. In the setting of CKD, numerous confounders may affect the legitimacy of the HbA1c assay 24 and HOMA-IR.…”
Section: Discussionsupporting
confidence: 52%
“…21 The high rates seen in the current study and in the AASK study (which was restricted to patients with both CKD and hypertension) are not surprising, as hypertension, CKD, and diabetes share common risk factors. The relatively low level of concordance among the measures of baseline glycemic control, consistent with other studies in high-risk 22 and patient (post-MI) 23 populations, raises questions about the best measure to use to characterize glycemic control status in persons with CKD. In the setting of CKD, numerous confounders may affect the legitimacy of the HbA1c assay 24 and HOMA-IR.…”
Section: Discussionsupporting
confidence: 52%
“…However, similarly to studies (3-5), C-peptide was not measured, and longitudinal data were not available. Other studies reported separate analyses for some prediabetes categories (32)(33)(34)(35)(36)(37). However, the focus was typically not on the assessment of glucose metabolism, thus the analysis of insulin sensitivity and beta-cell function was limited or absent.…”
Section: Discussionmentioning
confidence: 99%
“…Studies performing fasting glucose, OGTT, and HbA1c have shown discordance when categorizing test results in normal, pre‐DM, and DM, and HbA1c has a low sensitivity for diagnosing prediabetes and diabetes when compared to fasting glucose and OGTT …”
Section: Diagnostic Discordancementioning
confidence: 99%